Increased Intracellular Oxygen Radical Production in Neutrophils During Febrile Episodes of Periodic Fever, Aphthous Stomatitis, Pharyngitis, and Cervical Adenitis Syndrome. Issue 11 (28th October 2013) - Sundqvist, Martina; Wekell, Per; Osla, Veronica; Bylund, Johan; Christenson, Karin; Sävman, Karin; Foell, Dirk; Cabral, David A.; Fasth, Anders; Berg, Stefan; Brown, Kelly L.; Karlsson, Anna
Abstract : Objective: Periodic fever, aphthous stomatitis, pharyngitis, and cervical adenitis (PFAPA) syndrome is an autoinflammatory disease of unknown etiology that primarily affects preschool‐aged children. PFAPA syndrome is characterized by recurrent attacks of fever and symptoms of inflammation consistent with the disease acronym. Since autoinflammatory diseases are, by definition, mediated by cells of the innate immune system, the aim of this study was to evaluate the functional features of neutrophils, the most abundant innate immune cell in the circulation, in children with PFAPA syndrome. Methods: Blood polymorphonuclear leukocytes (PMNs), obtained from patients with PFAPA syndrome during both febrile and asymptomatic, afebrile phases of the disease, as well as from healthy children (afebrile controls) and children with fever and abdominal pain (febrile controls), were analyzed for 3 key neutrophil characteristics: 1) apoptosis (measured by annexin V/7‐aminoactinomycin D staining), 2) production of reactive oxygen species (ROS) (measured by luminol/isoluminol‐amplified chemiluminescence), and 3) priming status (measured as responsiveness to galectin‐3 and up‐regulation of CD11b). Results: Compared to PMNs obtained from patients with PFAPA syndrome during an afebrile interval and those from febrile controls, PMNs obtained from patients during a PFAPA syndrome flare produced elevated levels of intracellular NADPH oxidase–derived ROS, had significantly diminished rates of spontaneous apoptosis, and displayed signatures of priming. In contrast, PMNs from afebrile patients with PFAPA syndrome had a significantly elevated rate of spontaneous apoptosis compared to PMNs from afebrile controls. Conclusion: These findings demonstrate that 3 key aspects of neutrophil innate immune function, namely, apoptosis, priming, and generation of an intracellular oxidative burst, are altered, most prominently during febrile attacks, in children with PFAPA syndrome.